Processing of Cu-Cr alloy for combined high strength and high conductivity - Olofinjana and, A.O; Tan, A.; K. S. (Universitas Gadjah Mada, 1985)
High strength and high conductivity (HSHC) are two intrinsic properties difficult to combine in metallic alloy design because; almost all strengthening mechanisms also lead to reduced conductivity. Precipitation hardening by nano-sized precipitates had proven to be the most adequate way to achieve the optimum combination of strength and conductivity in copper based alloys. However, established precipitation strengthened Cu- alloys are limited to very dilute concentration of solutes thereby limiting the volume proportion hardening precipitates. In this work, we report the investigation of the reprocessing of higher Cr concentration Cu- based alloys via rapid solidification. It is found that the rapid solidification in the as-cast ribbon imposed combined solution extension and ultra-refinement of Cr rich phases. X-ray diffraction evidences suggest that the solid solution extension was up to 6wt%Cr. Lattice parameters determined confirmed the many folds extension of solid solution of Cr in Cu. Thermal aging studies of the cast ribbons indicated that peak aging treatments occurred in about twenty minutes. Peak aged hardness ranged from about 200 to well over 300Hv. The maximum peak aged hardness of 380Hv was obtained for alloy containing 6wt.%Cr but with conductivity of about 50%IACS. The best combined strength/conductivity was obtained for 4wt.%Cr alloy with hardness of 350HV and conductivity of 80% IACS. The high strengths observed are attributed to the increased volume proportion of semi-coherent Cr rich nano-sized precipitates that evolved from the supersaturated solid solution of Cu-Cr that was achieved from the high cooling rates imposed by the ribbon casting process. The rapid overaging of the high Cr concentration Cu-Cr alloy is still a cause for concern in optimising the process for reaching peak HSHC properties. It is still important to investigate a microstructural design to slow or severely restrict the overaging process. The optimum HSHC property reported here is a rare combination of high strength (>350Hv 900MPa) and conductivity (50 – 80% IACS) found in metallic alloys.